PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP FINANCIAL REPORTING LAG - Anggriani, Febry; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to examine the influence of corporate governance mechanism and financialperformance to the lag of the publication of financial statement (financial reporting lag) on every companysectors which are listed in Indonesia Stock Exchange in 2012-2014 periods. The sample has been carried out byusing stratified random sampling method and the collection technique has been selected 25% of go publiccompanies, and the number of observations is 269 annual financial statements which have been issued by theircompany have been retrieved from official website of Indonesia Stock Exchange (www.idx.co.id). Theexamination has been done by using multiple regressions analysis technique and instrument SPSS (StatisticalPackage for Social Science) 18 version, and the independent variables i.e. independent commissioner,managerial ownership, institutional ownership, the size of audit committee, meeting of audit committee,profitability, financial leverage, and liquidity to the dependent variable which is lag of the publication offinancial statement. The result of the research shows that the size of audit committee, meeting of auditcommittee, profitability, financial leverage, and liquidity have negative influence to the lag of the publication offinancial statement whereas independent commissioner, managerial ownership, institutional ownership do nothave any influence to the lag of the publication of financial statement with the contribution of the value ofAdjusted R square 57.3%.Keywords : financial reporting lag, time delay of publication, corporate governance, financial performance